An overview of possible solutions putting an end to the COVID-19 pandemic: COVID-19 solutions - Adiban Afkham, Saina; Hessami, Amirhossein; Saghazadeh, Amene; Rezaei, Nima (Acta Biomedica Atenei Parmensis, 2022)
In early 2020, a novel coronavirus, SARS-CoV2, started to spread throughout the world. The World Health Organization (WHO) declared the coronavirus disease 2019 (COVID-19) as a pandemic on March 5, 2020. This 2020’s pandemic has to date caused about 200,000 deaths and is still affecting the lives of people worldwide. No solitary solution can overcome the multidimensional challenges associated with the problem of COVID-19. Here, we provide a rapid overview of possible solutions offered by the epidemiological, pharmacological, immunological, and artificial intelligence fields of science on the COVID-19 pandemic. The simultaneous application of all these solutions might bring the world close to an end to the COVID-19 pandemic.